A 125 steel grade sulphur resistant pipe and its method of manufacture
Patent Information
- Application Number
- CN202311271662.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-09-28
AI Technical Summary
[0003]基于深井管柱悬重、耐内压及抗挤毁设计的需求,对油井管的强度要求也在不断提高,但目前采用110钢级抗硫油井管已无法满足含S超深井设计安全系数要求,随着我国西部地区深层油气开采的不断深入,管材失效问题频繁发生,从而带来巨大经济损失
[0021]1、本发明提供的125钢级抗硫管材通过精确控制钢中C、Si、Mn、V、Mo等元素的质量百分比,并结合淬火和回火的工艺,保证了所得抗硫管材中的组织为回火索氏体、残余奥氏体、富铜相以及基体上分布的弥散的、细化的第二相。所得抗硫管材具有较高强度水平的同时,兼具较高的韧性以及较好的抗SSCC性能,保证其能够满足更高的应用环境。
Smart Images

Figure CN117821861B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sulfur-resistant pipe technology, and in particular to a 125 steel grade sulfur-resistant pipe and its preparation method. Background Technology
[0002] Currently, oil and gas extraction depths in western my country have reached 5000–7000 meters, with some areas reaching 8000 meters. Along with increasing well depth, formation and even oil and gas pressures also continuously increase, with bottomhole pressures often reaching hundreds of megapascals. Pipes are one of the crucial components in oil and gas extraction, primarily operating in wet hydrogen sulfide environments. Stress corrosion cracking (SSC) is the greatest threat to the safe production of sulfur-containing oil and gas wells. Downhole, oil pipes not only face high temperatures and pressures but also challenges from H2S and Cl... - It is subjected to the combined effects of corrosive media, as well as tensile, compressive, torsional, bending and even various alternating loads, making its service environment extremely harsh.
[0003] Due to the design requirements for the suspension of deep well tubing, internal pressure resistance, and crush resistance, the strength requirements for oil well tubing are constantly increasing. However, the use of 110 grade sulfur-resistant oil well tubing can no longer meet the safety factor requirements for ultra-deep wells containing sulfur. With the continuous development of deep oil and gas extraction in western my country, tubing failures occur frequently, resulting in huge economic losses.
[0004] Therefore, there is an urgent need for a sulfur-resistant pipe with strong comprehensive performance that can be used under more severe conditions. Summary of the Invention
[0005] Based on the above analysis, the present invention aims to provide a 125 steel grade anti-sulfur pipe and its preparation method, thereby obtaining an anti-sulfur pipe with high comprehensive performance.
[0006] On the one hand, the present invention provides a 125 steel grade anti-sulfur pipe, the composition of which, by mass percentage, includes C: 0.09-0.12%, Si: 0.1-0.2%, Mn: 3.6-4.2%, P≤0.010%, S: ≤0.005%, Mo: 0.30-0.50%, Cr: 1.0-1.2%, V: 0.30%-0.40%, Ni: 1.0-2.0%, Cu: 1.0-2.0%, with the balance being Fe and unavoidable impurities.
[0007] Furthermore, the composition of the 125 steel grade anti-sulfur pipe material, by mass percentage, is as follows: C: 0.10-0.12%, Si: 0.1-0.2%, Mn: 3.8-4.2%, P≤0.010%, S: ≤0.004%, Mo: 0.30-0.50%, Cr: 1.0-1.2%, V: 0.30%-0.40%, Ni: 1.5-1.8%, Cu: 1.5-2.0%, with the balance being Fe and unavoidable impurities.
[0008] Furthermore, the internal structure of the sulfur-resistant pipe is described as tempered sorbite, retained austenite, and a dispersed, refined second phase distributed on the matrix.
[0009] Furthermore, the volume fraction of the retained austenite is ≥5%.
[0010] Furthermore, the internal structure of the sulfur-resistant pipe also contains a copper-rich phase.
[0011] Furthermore, the second phase includes VC, V8C7, and Cr. 23 C6 and Mo7C3.
[0012] Furthermore, the grain size of the sulfur-resistant pipe is less than 30 μm.
[0013] Preferably, the grain size of the sulfur-resistant pipe is 10-30 μm.
[0014] On the other hand, the present invention provides a method for preparing 125 grade sulfur-resistant pipe, comprising the following steps:
[0015] S1: Smelting and casting to obtain billets or ingots;
[0016] S2: The rough tube is obtained by rolling after high-temperature homogenization treatment of the billet or ingot;
[0017] S3: Quenching and high-temperature tempering are performed on the raw pipe to obtain sulfur-resistant pipe.
[0018] Further, in step S2, the billet or ingot is heated to 1120-1150°C in a heating furnace and held for 0.5-2 hours.
[0019] Furthermore, the quenching heating temperature is 800-860℃, and the quenching holding time is 0.5-2h; the tempering heating temperature is 640-680℃, the tempering holding time is 2-5h, and the mixture is air-cooled to room temperature.
[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0021] 1. The 125-grade sulfur-resistant pipe provided by this invention, through precise control of the mass percentages of elements such as C, Si, Mn, V, and Mo in the steel, combined with quenching and tempering processes, ensures that the microstructure of the resulting sulfur-resistant pipe consists of tempered sorbite, retained austenite, copper-rich phase, and dispersed, refined second phases distributed on the matrix. The resulting sulfur-resistant pipe possesses high strength while also exhibiting high toughness and good resistance to SSCC, ensuring its ability to meet higher application environments.
[0022] 2. This invention provides a method for preparing sulfur-resistant pipes. After high-temperature homogenization treatment, the pipes are rolled, followed by quenching and tempering to obtain a microstructure consisting of tempered sorbite, retained austenite, a copper-rich phase, and a second phase. The retained austenite has a volume fraction ≥5%, resulting in sulfur-resistant pipes with excellent strength and toughness matching, delayed crack propagation, and the austenite exhibits an FCC structure with significantly higher hydrogen solubility than the BCC structure of the matrix. This allows the austenite to act as a hydrogen trap, adsorbing more hydrogen and improving the matrix's resistance to SSCC.
[0023] 3. The sulfur-resistant pipe material prepared using the components and preparation method of this invention has good comprehensive mechanical properties, with a yield strength ≥869MPa, tensile strength ≥972MPa, elongation ≥18%, and room temperature impact energy ≥125J, which fully meets the safety requirements of high-grade steel tubing or casing. Referring to the NACE TM0177-2016 standard, it has passed the test of method A solution B, H2S partial pressure of 10kPa, and test temperature of 24℃.
[0024] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from the description and drawings, which are particularly pointed out. Attached Figure Description
[0025] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0026] Figure 1 The microstructure of Example 1;
[0027] Figure 2 The microstructure of Example 3;
[0028] Figure 3 The microstructure of Example 5;
[0029] Figure 4 This is the microstructure of Example 8. Detailed Implementation
[0030] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0031] Sulfur-resistant pipes are mainly used in oil and gas extraction, where they must withstand not only high pressure but also H2S and Cl. - To prevent corrosion by corrosive media, this invention provides a 125 steel grade sulfur-resistant pipe with high overall performance.
[0032] The 125 grade anti-sulfur pipe, by mass percentage, comprises C: 0.09–0.12%, Si: 0.1–0.2%, Mn: 3.6–4.2%, P ≤ 0.010%, S: ≤ 0.005%, Mo: 0.30–0.50%, Cr: 1.0–1.2%, V: 0.30%–0.40%, Ni: 1.0–2.0%, Cu: 1.0–2.0%, with the balance being Fe and unavoidable impurities.
[0033] Compared with existing technologies, this invention precisely controls the mass percentage of elements such as C, Si, Mn, V, and Mo in the steel. Through the direct interaction of these elements, after quenching and tempering, the microstructure of the sulfur-resistant pipe consists of tempered sorbite, retained austenite, copper-rich phase, and a dispersed, refined second phase distributed in the matrix. This not only ensures that the 125 steel-grade sulfur-resistant pipe has a high strength level, but also has high toughness and good anti-SSCC performance. This ensures that the resulting sulfur-resistant pipe can meet excellent mechanical properties and is suitable for use in more demanding and harsher working conditions.
[0034] The following details the function and dosage selection of the components contained in this invention:
[0035] Carbon (C) is a typical interstitial solid solution strengthening element. Increasing the carbon content in an alloy is an effective way to improve its strength. However, excessive C content will reduce the ductility and toughness of the steel. Furthermore, too much C and Mn can lead to banded structures in the steel. Banded structures are detrimental to the anti-SSCC performance of sulfur-resistant pipes. Also, excessively high C content can lead to excessively high strength; the higher the strength, the higher the susceptibility to hydrogen-induced cracking, which is also detrimental to the anti-SSCC performance of sulfur-resistant pipes.
[0036] Si: Silicon is a deoxidizer in steelmaking, but when the silicon content in anti-sulfur pipes is too high, it reduces the pipes' ability to resist hydrogen sulfide corrosion.
[0037] Mn (manganese): Manganese can lower the martensitic transformation temperature (Ms) and increase the content of retained austenite, especially when the Mn content in steel is ≥3%, it can also effectively improve the resistance to decomposition of retained austenite. However, a high Mn content will increase the volume fraction of retained austenite, which will reduce its stability. Some retained austenite will transform into martensite under certain conditions. Martensite has extremely poor resistance to SSCC (Superficial Solid-State Crack), high hardness, and high sensitivity to hydrogen-induced cracking, which is detrimental to the SSCC resistance of pipes. C (carbon) and Mn have a certain synergistic effect, easily forming banded structures, which is also detrimental to the SSCC resistance of sulfur-resistant pipes.
[0038] S: Sulfur severely degrades the corrosion resistance and toughness of sulfur-resistant pipes, and is very likely to form MnS inclusions that worsen SSCC performance. Therefore, its content needs to be controlled below 0.005%.
[0039] Cr and Mo: Chromium and molybdenum elements improve the hardenability of sulfur-resistant pipes, ensuring a fully martensitic structure during quenching. Simultaneously, Mo enhances the tempering stability of the steel during high-temperature tempering, preventing the sulfur-resistant pipes from experiencing excessive strength loss during tempering, thus ensuring good overall mechanical properties at high strength. Mo and Cr are also excellent elements for resisting uniform corrosion, reducing H... + The amount of sulfur-resistant pipe material penetrated from the pitted surface indirectly improved its resistance to SSCC.
[0040] Vanadium (V): Vanadium precipitates as vitamin C during quenching, which refines grains by pinning grain boundaries. During heat treatment and tempering, it forms carbides, resulting in precipitation strengthening and improved resistance to high-temperature tempering. Furthermore, the combination of V and C to precipitate carbides reduces the dissolved C content in the steel, decreasing the appearance of banded structures and reducing SSCC susceptibility. However, excessively high V content in the steel significantly reduces the material's toughness.
[0041] Ni: Nickel expands the austenite phase region and is a major alloying element for forming and stabilizing austenite, improving the stability of retained austenite at room temperature. Ni can synergistically work with Cr and Mo to improve hardenability and corrosion resistance. Meanwhile, because Cu is prone to embrittlement in steel, it is necessary to add Ni to the steel at a content higher than half that of Cu. Therefore, in this invention, Ni is added at a ratio of 1:1 to Cu, with a Ni content of 1.0–2.0%.
[0042] Cu: Copper can form a copper-rich phase in sulfur-resistant pipes, which is a typical FCC structure. The solubility of hydrogen in the FCC structure is much higher than that in the matrix BCC structure. Therefore, both the copper-rich phase and the retained austenite can dissolve a large amount of hydrogen. + This improves the pipe's resistance to SSCC.
[0043] Preferably, the 125 steel grade anti-sulfur pipe comprises, by mass percentage: C: 0.10-0.12%, Si: 0.1-0.2%, Mn: 3.8-4.2%, P≤0.010%, S: ≤0.004%, Mo: 0.30-0.50%, Cr: 1.0-1.2%, V: 0.30%-0.40%, Ni: 1.5-1.8%, Cu: 1.5-2.0%, with the balance being Fe and unavoidable impurities.
[0044] This invention provides a method for preparing 125 grade sulfur-resistant pipe, comprising the following steps:
[0045] S1: Smelting and casting to obtain billets or ingots;
[0046] S2: The rough tube is obtained by rolling after high-temperature homogenization treatment of the billet or ingot;
[0047] S3: Quenching and high-temperature tempering are performed on the raw pipe to obtain sulfur-resistant pipe.
[0048] Specifically, in step S1, a converter, electric furnace or induction furnace can be used for smelting, and continuous casting can be used to produce billets or ingot casting can be used to produce ingots.
[0049] Specifically, in step S2, the billet or ingot is heated to 1120-1150°C in a heating furnace and held for 0.5-2 hours.
[0050] During high-temperature homogenization treatment, it is ensured that all alloying elements are dissolved and exist in the matrix in a solid solution state. However, when the holding temperature is too high or the holding time is too long, the austenite grains grow excessively or even overheat, reducing the final performance of the anti-sulfur pipe. When the holding temperature is too low or the holding time is too short, the anti-sulfur pipe cannot be completely austenitized or the alloying elements are not fully dissolved, resulting in uneven composition of the anti-sulfur pipe and affecting its performance.
[0051] Specifically, in step S2, after rolling, water spray cooling is used to form a rough tube.
[0052] Specifically, in step S2, the final rolling temperature is 850-900℃ to ensure that a certain amount of VC is precipitated during the rolling process.
[0053] Specifically, in step S3, the quenching heating temperature is 800-860℃, and the quenching holding time is 0.5-2h; the tempering heating temperature is 640-680℃, the tempering holding time is 2-5h, and the mixture is air-cooled to room temperature.
[0054] Quenching involves heating the rough tube to its full austenitizing temperature of 800–860℃, controlling the heating rate at 1–4℃ / s, and holding it at that temperature for 0.5–2 hours. This ensures complete austenitization of the sulfur-resistant tube microstructure and simultaneously precipitates second-phase VC particles, pinning grain boundaries and preventing grain growth, thus refining the grains and improving resistance to SSCC (sulfur-resistant corrosive cancer). Quenching to room temperature yields a fully martensitic microstructure. Although grain boundary growth is not significant due to VC precipitation and pinning, excessively high temperatures or excessively long holding times have little impact on the final performance but may reduce production efficiency. Conversely, excessively low holding temperatures or insufficient holding times result in incomplete austenitization of the sulfur-resistant tube, leading to an uneven microstructure and affecting performance.
[0055] Specifically, the internal structure of the sulfur-resistant pipe consists of tempered sorbite, retained austenite, copper-rich phase, and a dispersed, refined second phase distributed on the matrix.
[0056] After tempering, the quenched martensite structure transforms into fine tempered sorbite structure, and some martensite undergoes reverse phase transformation into austenite. After air cooling, the reverse phase transformation austenite does not undergo phase transformation and is retained. The volume fraction of retained austenite is ≥5%, and the comprehensive mechanical properties and anti-SSCC properties are significantly improved.
[0057] Preferably, the volume fraction of the retained austenite is 8% to 14%.
[0058] When the tempering temperature reaches 680℃ and is held for more than 3 hours, a copper-rich phase is formed. As an FCC structure, the copper-rich phase can not only improve the toughness of the material, but also dissolve H, just like the retained austenite. + Its properties are far superior to those of tempered sorbite matrix of BCC.
[0059] Specifically, the second phase mainly includes VC, V8C7, and Cr. 23 C6, Mo7C3.
[0060] VC can be dispersed and precipitated in large quantities. The second-phase particles of VC can act as hydrogen traps, adsorbing a large amount of H₂. + Reduce H in the matrix + Concentration improves resistance to SSCC. Furthermore, the second-phase VC particles are primarily nanoscale in size, mainly spherical or short rod-shaped, thus allowing for the absorption of large amounts of H₂. + It is extremely difficult to use VC as a hydrogen-induced crack initiation point when it is adsorbed on VC particles.
[0061] Specifically, the grain size of the sulfur-resistant pipe is less than 30 μm.
[0062] Preferably, the grain size of the sulfur-resistant pipe is 10-30 μm.
[0063] Specifically, the sulfur-resistant pipe material has a yield strength ≥869MPa, tensile strength ≥972MPa, elongation ≥18%, and room temperature impact energy ≥125J, fully meeting the safety requirements of high-grade steel tubing or casing. Referring to NACE TM0177-2016 standard, it has passed testing using method A with solution B, an H2S partial pressure of 10kPa, and an experimental temperature of 24℃.
[0064] To more clearly describe the present invention, the following embodiments and comparative examples are provided for further illustration.
[0065] Example
[0066] Examples 1-8 of this invention provide a method for preparing 125 grade sulfur-resistant pipe. The steel components in Examples 1-8, by mass percentage, include C: 0.09-0.12%, Si: 0.1-0.2%, Mn: 3.6-4.2%, P≤0.010%, S: ≤0.005%, Mo: 0.30-0.50%, Cr: 1.0-1.2%, V: 0.30%-0.40%, Ni: 1.0-2.0%, Cu: 1.0-2.0%, with the balance being Fe and unavoidable impurities.
[0067] The methods for preparing the steels in Examples 1-8 and Comparative Examples 1-3 include:
[0068] S1: Steel is produced by converter steelmaking and continuous casting to produce billets;
[0069] S2: The billet is heated to the homogenization temperature, kept at the constant temperature for a period of time, and then rolled. When the final rolling temperature reaches a certain temperature, water spray cooling is used to form a rough tube.
[0070] S3: Heat the rough tube to the quenching temperature, hold it at that temperature for a certain time, and then quench it in water to room temperature; then heat the quenched rough tube to a certain tempering temperature, hold it at that temperature for a certain time, and then air cool it to room temperature to finally obtain sulfur-resistant pipe.
[0071] The specific preparation methods of the sulfur-resistant pipes in Examples 1-8 are shown in Table 1 below, the corresponding components are shown in Table 2, the microstructure is shown in Table 3, the mechanical properties are shown in Table 4, and the SSCC resistance is shown in Table 5. The microstructure of Example 1 is as follows... Figure 1 As shown, the microstructure of Example 3 is as follows Figure 2 As shown, the microstructure of Example 5 is as follows: Figure 3 As shown, the microstructure of Example 8 is as follows Figure 4 As shown.
[0072] Table 1. Preparation methods of Examples 1-8 and Comparative Examples 1-3
[0073]
[0074] Table 2 Chemical composition of Examples 1-8 and Comparative Examples 1-3
[0075] Example 1 0.09 0.11 3.6 0.008 0.004 1.11 0.37 0.33 1.54 1.57 Example 2 0.09 0.20 3.6 0.007 0.004 1.20 0.32 0.35 1.91 1.85 Example 3 0.10 0.11 4.1 0.009 0.003 1.04 0.40 0.31 1.07 1.04 Example 4 0.12 0.15 3.6 0.006 0.004 1.13 0.31 0.37 1.43 1.48 Example 5 0.09 0.10 4.2 0.008 0.003 1.17 0.35 0.35 1.98 1.95 Example 6 0.09 0.11 3.8 0.005 0.003 1.14 0.42 0.33 1.17 1.09 Example 7 0.11 0.20 4.1 0.006 0.003 1.15 0.36 0.34 1.41 1.26 Example 8 0.11 0.10 3.7 0.007 0.004 1.13 0.39 0.31 1.73 1.61 Comparative Example 1 0.11 0.10 3.7 0.007 0.004 1.13 0.39 0.31 1.73 1.61 Comparative Example 2 0.08 0.10 4.2 0.008 0.003 1.17 0.35 0.35 1.98 1.95 Comparative Example 3 0.15 0.20 1.5 0.010 0.008 1.01 0.65 0.13 0.54 /
[0076] Table 3 Microstructure of Examples 1-8 and Comparative Examples 1-3
[0077]
[0078]
[0079] Table 4 Mechanical properties of steels from Examples 1-8 and Comparative Examples 1-3
[0080]
[0081] Table 5. SSCC resistance of Examples 1-8 and Comparative Examples 1-3
[0082]
[0083]
[0084] Referring to Examples 1-8 and Comparative Examples 1-3, and in conjunction with Tables 1-5 and Figure 1-4 It can be seen that the composition and preparation process of Examples 1-8 provided by the present invention result in anti-sulfur pipes with internal structure consisting of tempered sorbite, 8% to 14% residual austenite and second phase by volume. The pipes have high tensile strength, yield strength and impact energy, and have passed the test of anti-SSCC performance, without breaking after 720 hours of testing.
[0085] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A sulfur-resistant pipe of grade 125 steel, characterized in that, Its composition, by mass percentage, includes C: 0.09~0.12%, Si: 0.1~0.2%, Mn: 3.6~4.2%, P≤0.010%, S: ≤0.005%, Mo: 0.30~0.50%, Cr: 1.0~1.2%, V: 0.30%~0.40%, Ni: 1.0~2.0%, Cu: 1.04~2.0%, with the balance being Fe and unavoidable impurities; The internal microstructure of the sulfur-resistant pipe consists of tempered sorbite, retained austenite, and a dispersed, refined second phase distributed on the matrix; the internal microstructure of the sulfur-resistant pipe also contains a copper-rich phase; wherein the second phase includes VC, V8C7, and Cr. 23 C6 and Mo7C3; the volume fraction of the retained austenite is ≥5%; The sulfur-resistant pipe is made by quenching and tempering, wherein the quenching temperature is 800~860℃ and the tempering temperature is 660~680℃; the grain size of the sulfur-resistant pipe is less than 30μm.
2. The 125 grade sulfur-resistant pipe according to claim 1, characterized in that, Its composition, by mass percentage, is as follows: C: 0.10~0.12%, Si: 0.1~0.2%, Mn: 3.8~4.2%, P≤0.010%, S: ≤0.004%, Mo: 0.30~0.50%, Cr: 1.0~1.2%, V: 0.30%~0.40%, Ni: 1.5~1.8%, Cu: 1.5~2.0%, with the balance being Fe and unavoidable impurities.
3. The 125 grade anti-sulfur pipe according to claim 1, characterized in that, The volume fraction of the retained austenite is 8-14%.
4. The 125 grade sulfur-resistant pipe according to claim 1, characterized in that, The grain size of the sulfur-resistant pipe is 10-30 μm.
5. The method for preparing the 125 steel grade sulfur-resistant pipe according to any one of claims 1-4, characterized in that, Includes the following steps: S1: Smelting and casting to obtain billets or ingots; S2: The rough tube is obtained by rolling after high-temperature homogenization treatment of the billet or ingot; S3: Quenching and high-temperature tempering are performed on the raw pipe to obtain sulfur-resistant pipe.
6. The method for preparing the 125 steel grade sulfur-resistant pipe according to claim 5, characterized in that, In step S2, the billet or ingot is heated to 1120-1150°C in a heating furnace and held for 0.5-2 hours.
7. The method for preparing the 125 grade sulfur-resistant pipe according to claim 5, characterized in that, The quenching temperature is 800~860℃, and the quenching holding time is 0.5~2h; the tempering temperature is 660~680℃, the tempering holding time is 2~5h, and then air-cooled to room temperature.
Citation Information
Patent Citations
High-strength hydrogen sulfide corrosion resistant oil well pipe steel and preparation method thereof
CN111074155A
